Evacuación endoscópica de hematoma subdural crónico sin intubación orotraqueal - Villalonga, Juan Francisco; Ramírez Abrego, Leonel; Tafur Tatis, Zamir; Ulloque-Caamaño, Liezel; Robles, Matías; Campero, Álvaro (Revista Argentina de Neurocirugía, 2024)
ABSTRACTIntroduction: The endoscopic evacuation of chronic subdural hematomas (CSDH) began in 1990, and thanks to the development of anesthetic techniques, various neurosurgical interventions have been performimg with the patient awake, this technique could be useful in elderly patients to reduce their morbidity and mortality.The aim of this paper is to describe step-by-step surgical technique for endoscopic evacuation of CSDH in an awake patient and to present illustrative cases.Material and methods: To develop the "surgical technique" section, the following were analyzed: operative protocols, videos of surgeries and photos of surgeries performed in Tucumán by our team in 2022. For the presentation of illustrative cases, a retrospective study of patients with diagnosis of CSDH operated in our institution.Results: The anesthetic and surgical technique is described step by step with all the tips.Conclusion: The technique for CSDH was presented as it is performed by our team on a daily basis. The same was illustrated.Keywords: Subdural hematoma. Endoscopy. Dexmedetomidine. Sclap. Blocking.